2017
DOI: 10.1002/ab.21701
|View full text |Cite
|
Sign up to set email alerts
|

Psychological processes in young bullies versus bully‐victims

Abstract: Some children who bully others are also victimized themselves (“bully‐victims”) whereas others are not victimized themselves (“bullies”). These subgroups have been shown to differ in their social functioning as early as in kindergarten. What is less clear are the motives that underlie the bullying behavior of young bullies and bully‐victims. The present study examined whether bullies have proactive motives for aggression and anticipate to feel happy after victimizing others, whereas bully‐victims have reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
2
25
1
8
Order By: Relevance
“…Aggressive-victims appeared to share many similar social–emotional and social–cognitive characteristics as aggressors. These findings are consistent with a shared processes hypothesis (see van Dijk, Poorthuis, & Malti, 2017), according to which aggressive-victims and aggressors have similar psychological profiles. However, it appeared that the distinction between these aggressive subgroups emerged more clearly with respect to their peer relationships such that aggressive-victims also exhibited comparable relational risks as victims.…”
Section: Discussionsupporting
confidence: 89%
“…Aggressive-victims appeared to share many similar social–emotional and social–cognitive characteristics as aggressors. These findings are consistent with a shared processes hypothesis (see van Dijk, Poorthuis, & Malti, 2017), according to which aggressive-victims and aggressors have similar psychological profiles. However, it appeared that the distinction between these aggressive subgroups emerged more clearly with respect to their peer relationships such that aggressive-victims also exhibited comparable relational risks as victims.…”
Section: Discussionsupporting
confidence: 89%
“…We assessed children's hostile attributional bias using four vignettes that describe ambiguous provocations by a same-gender peer (Dodge, McClaskey, & Feldman, 1985;Feshbach, 1989;Van Dijk, Poorthuis, & Malti, 2017). Story themes were (a) being hurt; (b) one's drawing being ruined; (c) being refused to join a board game; (d) one's toy being taken.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that hard-to-manage preschoolers with poor mind skills tend to behave more negatively towards their peers (i.e., they showed more insulting, whining, and controlling behavior while playing games). Children may bully others because they insufficiently comprehend their peers' mental states (Van Dijk, Poorthuis, and Malti, 2017).…”
Section: Brain Studies and Psychologymentioning
confidence: 99%
“…Bullies may tend to anticipate feeling positive emotions after victimizing others. Such "happy victimizer emotions" are uniquely related to proactive aggression (Van Dijk, Poorthuis, and Malti, 2017). Furthermore, bullies employ moral disengagement mechanisms that allow them to engage with violent conduct (Gini, 2006).…”
Section: Risk Takingmentioning
confidence: 99%